Assessing the overall benefits of programs enhancing human capital and equity: A new method with an application to school meals - Alderman, Harold; Aurino, Elisabetta; Baffour, Priscilla Twumasi; Gelli, Aulo; Turkson, Festus Ebo; Wong, Brad (Elsevier, 2025)
Poverty reduction and nutrition are often joint outcomes of many public policies and programs which have education as their primary outcome. Quantification of overall benefits for these programs in a common metric is challenging. We propose a new method to incorporate distributional benefits from poverty reduction into standard education economic evaluations. We apply this to a randomized controlled trial (RCT) evaluating a large-scale school feeding program in Ghana. We first map effect sizes from the RCT in learning-adjusted years of schooling. We then convert these into long-term monetary gains from increased learning, to which we finally add the distributional benefits under different scenarios of inequality aversion preferences. We show that the program has substantial long-term economic gains. While these primarily stem from improved human capital, depending on different scenarios, up to half of total benefits are driven by current gains from the social protection transfer. Beyond school meals, our methodology is relevant to programs that have impacts covering both human capital and distributional benefits, and to economic evaluations beyond education.